2012
DOI: 10.1016/j.neuron.2011.09.034
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor-Mediated PIP5K Activation to Produce PI(4,5)P2 Is Essential for AMPA Receptor Endocytosis during LTD

Abstract: NMDA receptor activation leads to clathrin-dependent endocytosis of postsynaptic AMPA receptors. Although this process controls long-term depression (LTD) induction in the hippocampus, how it is regulated by neuronal activities is not completely clear. Here, we show that Ca²⁺ influx through the NMDA receptor activates calcineurin and protein phosphatase 1 to dephosphorylate phosphatidylinositol 4-phosphate 5-kinaseγ661 (PIP5Kγ661), the major phosphatidylinositol 4,5-bisphosphate (PI(4,5)P₂)-producing enzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 72 publications
1
60
0
Order By: Relevance
“…In agreement with previous reports (30,32), we found that the surface HA-GluR2 decreased rapidly following NMDA stimulation in WT but not in Prex1 −/− neurons ( Fig. 7 C and D).…”
Section: Significancesupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports (30,32), we found that the surface HA-GluR2 decreased rapidly following NMDA stimulation in WT but not in Prex1 −/− neurons ( Fig. 7 C and D).…”
Section: Significancesupporting
confidence: 93%
“…PP1 is a vital factor required for CA1 NMDAR-dependent LTD and AMPAR endocytosis (31,32). Previous findings have suggested that PP1α, the catalytic subunit of PP1, binds to the RVxF motif in the C-terminal IP4P domain of P-Rex1 and dephosphorylates adjacent serine residues in nonneuronal cells.…”
Section: Significancementioning
confidence: 99%
“…The AMPA receptor (AMPAR) complex containing dephosphorylated STG may be trapped in the endocytic zone as the complex undergoes lateral diffusion, when the negatively charged lipid PIP 2 , which is enriched at the endocytic zone, binds to dephosphorylated STG 13 . Calcineurin also activates production of PIP 2 at the endocytic zone as shown by the dotted arrow 26 . As AP-2 also binds PIP 2 and accumulates at the endocytic zone, the AMPAR complex then enters the clathrin-mediated endocytosis process as a result of the interaction between STG and AP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the critical function of Arf6 in the activation of the phosphatidylinositol 4,5-bisphosphate-synthesizing enzyme phosphatidylinositol 4-phosphate 5-kinase (PIP5K) 26 , Arf6 could control FGF-2 secretion through PIP5K activation. Of three PIP5K isozymes, PIP5Kg is specifically expressed in neurons 27 and its activation is dependent on its phosphorylation/ dephosphorylation state: the phosphorylated form of PIP5Kg present in resting cells is dephosphorylated on cellular stimulation to interact with AP-2 and talin, which then activate it 28,29 . However, it is unlikely that PIP5Kg is involved in Arf6-dependent FGF-2 secretion, as its phosphorylation status was not changed by neuronal Arf6 ablation ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%